Low-FODMAP Diet in the Treatment of Irritable Bowel Syndrome – Efficacy, Comparison with Other Diets, Mechanisms, and Clinical Applications - Strużek, Konrad; Karamus, Kornelia; Rejmak, Rafał; Biłogras, Jan; Borowska-Łygan, Martyna; Urban, Wojciech; Tomaszewski, Jakub (Journal of Education, Health and Sport, 2025)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder that significantly impacts patients' quality of life. One of the most frequently used and well-documented dietary approaches in the treatment of IBS is the low-FODMAP diet, which involves the elimination of fermentable oligosaccharides, disaccharides, monosaccharides, and polyols that can exacerbate gastrointestinal symptoms. This article presents the mechanisms of action of the FODMAP diet, its effectiveness, and a comparison with other dietary approaches used in IBS, such as the gluten-free and Mediterranean diets. The three-phase model of the diet, including the elimination, reintroduction, and personalization phases, is discussed, enabling dietary adaptation to individual patient tolerance. A review of studies has shown that the effectiveness of the FODMAP diet in reducing IBS symptoms ranges from 50% to 75%, making it one of the most effective dietary strategies for managing this condition. Additionally, potential biomarkers for dietary response, such as breath tests, gut microbiota analysis, and fecal and urinary metabolites, are explored to help identify patients who may benefit most from this approach. The article also emphasizes the importance of a multidisciplinary approach in IBS treatment, integrating dietary therapy, gastroenterological support, and psychological interventions. Despite the high efficacy of the FODMAP diet, its long-term consequences, particularly its impact on gut microbiota and metabolism, require further research. The article highlights the need for continued analysis of the diet’s lasting effects and its effectiveness in different IBS subtypes, which could contribute to even better personalization of therapeutic strategies to meet patients' individual needs.